(untitled) (International Journal of Islamic Business, 2019)
The objective of this study is to investgate some factors that influence the Islamic financial performance of Islamic bank Indonesia. The population in this research uses all Sharia Commercial Banks published by Bank Indonesia in 2011-2016. The purposive sampling technique used as the sampling method. A total of 48 annual reports have been analyzed using circular causation models The finding of this research shows that the Good Corporate Governance influence the Profit Sharing Ratio, Zakat Performance Ratio, while the Profit Sharing Ratio, Zakat Performance Ratio affected the Good Corporate Governance. The variable of Corporate Social Responsibility affected the Profit Sharing Ratio and Equitable Distribution Ratio, whereas Profit Sharing Ratio and Equitable Distribution Ratio affected the Corporate Social Responsibility. The variable of GCG has influenced on CSR and vice versa. This research finding provides managerial implications for Sharia banking. The Islamic financial performance can be used in tesing the ratios which are a reflection of business performance, as well as OJK (Financial Services Authority) the Sharia Performance Index can be used in making the policy for measuring the Financial Performance.